Comparing the Efficacy of Pamidronate and Thalidomide for the Treatment of Refractory Axial Spondyloarthritis: An Open Label Randomized Clinical Trial - Sultana, Nadia; Mahbubul Alam, A F M; Bandhan, Iftekhar Hussain Bandhan; Hasaan, Md Masudul; Rabbani, Md Golam; Kabir, Md Ekramul; Shahin, Md Abu; Choudhury, Minhaj Rahim; Atiqul Haq, Syed; Zaman, Mohammad Mostafa (Journal of Bangladesh College of Physicians and Surgeons, 2023)
Introduction: Spondyloarthritis (SpA) is a chronic systemic inflammatory rheumatic disease affecting sacroiliac joints, spine and peripheral joints. Pamidronate and thalidomide are proven to be effective in refractory axial SpA in some studies. This study aimed at comparing the efficacy and safety of pamidronate and thalidomide in refractory axial spondyloarthritis (SpA). Methods: This open label randomized clinical trial was conducted on refractory SpA patients at the department of rheumatology of Bangabandhu Sheikh Mujib Medical University, Dhaka. Pamidronate 60mg intravenous monthly and thalidomide 200mg/day were given to pamidronate and thalidomide groups, respectively for 6 months. Both groups received non-steroidal anti-inflammatory drugs and therapeutic exercises. More than 20% improvements in Assessment of Spondyloarthritis International Society (ASAS-20) at 6 months were considered as primary outcome measure. Secondary outcome measures included Bath ankylosing spondylitis disease activity index (BASDAI), Bath ankylosing spondylitis functional index (BASFI), Bath ankylosing spondylitis meteorological index (BASMI), patient global assessment, physician global assessment, erythrocyte sedimentation rate (ESR), C-reactive protein, ASAS 40 etc. Results: Significant improvement in ASAS 20 was observed in both pamidronate (76.9%) and thalidomide (85.2%) groups (P=0.501). Among the secondary outcome ASAS 40 response rates were 46.2% and 51.9% in the pamidronate and thalidomide groups respectively. All other secondary outcome indicators such as BASDAI, BASFI, BASMI etc. within-group showed significant improvements in both groups (P<0.001). Between-group differences were nonsignificant (P>0.1) except for ESR (P=0.006). There were no serious adverse events in any group. Conclusions: Pamidronate and thalidomide were effective in refractory axial SpA and were well tolerated. However, there was no significant difference in the efficacy of the two drugs. J Bangladesh Coll Phys Surg 2023; 41(4): 269-276